1993
DOI: 10.1111/j.1550-7408.1993.tb04916.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel Structure In the Pellicular Complex of Plasmodium Falciparum Gametocytes1

Abstract: Using transmission electron microscopy, transverse dense bands were found to be associated with subpellicular microtubules and inner membranes in Plasmodium falciparum gametocytes. These dense bands may act as supportive structures to maintain the parallel arrangement of the microtubules, and/or to connect them to the inner membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Similar patchworks of sub-pellicular membrane have been described in the IMC of the invasive stages of P. falciparum, as well as in Toxoplasma and other apicomplexa (Bannister et al, 2000;Raibaud et al, 2001). Another early transmission electron microscopy study identified protein 'crosslinks' running perpendicular to the microtubule network (Kaidoh et al, 1993). We suggest that the GAP50-GFP-labelled IMC 'stripes' represent IMC cisternae laid down as rectangular plates, whereas the gaps represent proteinaceous material that holds the cisternae and the microtubules in place.…”
Section: Discussionmentioning
confidence: 75%
“…Similar patchworks of sub-pellicular membrane have been described in the IMC of the invasive stages of P. falciparum, as well as in Toxoplasma and other apicomplexa (Bannister et al, 2000;Raibaud et al, 2001). Another early transmission electron microscopy study identified protein 'crosslinks' running perpendicular to the microtubule network (Kaidoh et al, 1993). We suggest that the GAP50-GFP-labelled IMC 'stripes' represent IMC cisternae laid down as rectangular plates, whereas the gaps represent proteinaceous material that holds the cisternae and the microtubules in place.…”
Section: Discussionmentioning
confidence: 75%
“…Until now it is poorly understood, how the IMC plates are joined together. A proteinaceous material in P. falciparum gametocytes has been identified by electron microscopy (Kaidoh et al ., ) and cryo‐electron tomography (Dearnley et al ., ) running perpendicular to the microtubule network and corresponding probably to the transverse sutures encircling the gametocytes (Meszoely et al ., ). It was recently suggested that these proteinaceous sutures might provide a means of stabilizing the IMC and the subpellicular microtubule network (Dearnley et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…2J,K). Plasmodium parasites lack an intact conoid, but retain the apical polar rings, which probably nucleate subpellicular microtubule polymerization (Russell and Sinden, 1982;Kaidoh et al, 1993). As daughter scaffolds elongate, DNA replication is completed, and the nucleus lobulates (Fig.…”
Section: Discussionmentioning
confidence: 99%